2014
DOI: 10.1111/evj.12284
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of conventional and hydrosurgical debridement methods in reducing Staphylococcus aureus inoculation of equine muscle in vitro

Abstract: SummaryReasons for performing study: The success of primary healing of equine traumatic wounds is dependent on thorough debridement. A specific hydrosurgical debridement device (Versajet TM ) a is gentle to viable tissues, yet effectively removes macroscopic contaminants and debris. We wished to investigate whether it is effective in reducing bacterial burden and whether it differs from traditional methods. No previous reports compare hydrosurgical debridement and conventional wound debridement with regard to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A randomized controlled trial in burn patients in which treatment with Versajet was compared to traditional debridement found no significant difference in postoperative pain, healing time, and contracture rate. 13 Overall, tangential excision of our patient's phymatous rosacea using the Versajet II Hydrosurgery System yielded excellent contouring. However, due to the paucity of literature on the subject, it is difficult to discern the optimal treatment modality.…”
Section: Commentmentioning
confidence: 75%
See 1 more Smart Citation
“…A randomized controlled trial in burn patients in which treatment with Versajet was compared to traditional debridement found no significant difference in postoperative pain, healing time, and contracture rate. 13 Overall, tangential excision of our patient's phymatous rosacea using the Versajet II Hydrosurgery System yielded excellent contouring. However, due to the paucity of literature on the subject, it is difficult to discern the optimal treatment modality.…”
Section: Commentmentioning
confidence: 75%
“…12 Hydrosurgical debridement also has been shown to reduce Staphylococcus aureus inoculate levels from in vitrocontaminated equine models significantly more than conventional debridement methods (P<.05). 13 Versajet surgery appears to be well tolerated, with side effects comparable to those of classic surgical excision. A randomized controlled trial in burn patients in which treatment with Versajet was compared to traditional debridement found no significant difference in postoperative pain, healing time, and contracture rate.…”
Section: Commentmentioning
confidence: 94%
“…Six veterinary publications were identified through the search. One met the inclusion criteria and was assessed using the GRADE framework 23 . This study measured Staphylococcus aureus colony forming units post debridement in equine cadaver muscle tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in equine wound research, no specific guidelines exist on debridement, so to follow the human guidelines seems valid. An equine ex vivo study showed better effectiveness of hydrosurgical debridement compared to normal sharp debridement [123], thus hydrosurgery might be a useful subcategory of surgical debridement. No matter the method, infected tissue should be debrided whenever possible, and debridement should always be combined with other anti-biofilm strategies, as not all of the biofilms and bacteria can be removed [10,27].…”
Section: Treatment Of Biofilm In Woundsmentioning
confidence: 97%